2008
DOI: 10.1103/physrevb.77.045212
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the statistical shift of Fermi level on the conductivity behavior in microcrystalline silicon

Abstract: The electrical conductivity behavior of highly crystallized undoped hydrogenated microcrystalline silicon (µc-Si:H) films having different microstructures was studied. The dark conductivity is seen to follow Meyer Neldel rule (MNR) in some films and anti MNR in others, depending on the details of microstructural attributes and corresponding changes in the effective density of states distributions. A band tail transport and statistical shift of Fermi level are used to explain the origin of MNR as well as anti-M… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 59 publications
2
15
0
Order By: Relevance
“…For E a between 0.2 and 0.6 eV ͑the region where shifts to mid gap͒ the material obeys the MNR. The corresponding Meyer-Neldel energy from the calculation is found to be 40 meV, which is consistent with values reported from experiments listed by Ram et al 30 The flat region above 0.5 eV in the calculated data is not very recognizable in the experimental data but is in fact found experimentally. The data of Kočka 2 show this most clearly.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…For E a between 0.2 and 0.6 eV ͑the region where shifts to mid gap͒ the material obeys the MNR. The corresponding Meyer-Neldel energy from the calculation is found to be 40 meV, which is consistent with values reported from experiments listed by Ram et al 30 The flat region above 0.5 eV in the calculated data is not very recognizable in the experimental data but is in fact found experimentally. The data of Kočka 2 show this most clearly.…”
Section: Resultssupporting
confidence: 80%
“…The lower E a ͑E a Ͻ 0.15 eV͒ which has been observed experimentally for very high X c , 30 can only be reproduced by the model if we decrease the effective barrier height by lowering the conduction path or changing the band alignment. This change in the a-Si barrier height may happen in reality by a change in band alignment, by accumulation of charged defects at the interfaces, or by thinning of the barrier which enables tunneling.…”
Section: Discussionmentioning
confidence: 93%
“…Similarly, negative slope for the function lnσ 0 = f(ΔE) has been observed in crystalline tetrahedrally bonded semiconductors (essentially silicon) having different grain size from macro (bulk, c-) to nano (n-) including the micro (μ-) range. Examples are in: undoped c-Si [43], μc-Si:H [50] and nc-Si [51] as well as for doped μc-Si:H [52]. Ram et al [52] states that both presence (E MN > 0) and absence (E MN b 0) of MNR can be seen in the dark conductivity behavior of highly crystalline single phase undoped μc-Si:H material, depending on the microstructure and the correlative DOS features.…”
Section: Discussionmentioning
confidence: 97%
“…Examples are in: undoped c-Si [43], μc-Si:H [50] and nc-Si [51] as well as for doped μc-Si:H [52]. Ram et al [52] states that both presence (E MN > 0) and absence (E MN b 0) of MNR can be seen in the dark conductivity behavior of highly crystalline single phase undoped μc-Si:H material, depending on the microstructure and the correlative DOS features. This study strongly indicates the presence of a band tail transition in μc-Si:H. These authors showed, also, that the statistical shift model can successfully explain both the presence (E MN > 0) and absence (E MN b 0) of MNR behavior in their heterogeneous μc-Si:H material.…”
Section: Discussionmentioning
confidence: 97%
“…5 shows the conductivity prefactor σ 0 as a function of the activation energy E a . The data from [29,30] are also reported for comparison. The data obtained from the SRC (2-4 nm) multilayers follow the Meyer-Neldel rule.…”
Section: Resultsmentioning
confidence: 98%